The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11999-015-4247-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher Preoperative Patient Activation Associated With Better Patient-reported Outcomes After Total Joint Arthroplasty

Abstract: Level II, prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 43 publications
1
55
0
2
Order By: Relevance
“…Measuring the effect of so-called ''patient activation'' on satisfaction, symptom intensity, and magnitude of disability after total hip and knee arthroplasty makes sense. Andrawis and colleagues found that patient activation was associated with pain, symptoms, mental health, and satisfaction, but not with activity/function/disability [1].…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring the effect of so-called ''patient activation'' on satisfaction, symptom intensity, and magnitude of disability after total hip and knee arthroplasty makes sense. Andrawis and colleagues found that patient activation was associated with pain, symptoms, mental health, and satisfaction, but not with activity/function/disability [1].…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Andrawis and colleagues note that satisfaction rates are around 85% for hip and knee arthroplasty [1]. Emotional health and resources explain much of the variation in symptom relief and magnitude of disability after arthroplasty [2][3][4].…”
mentioning
confidence: 99%
“…O ato cirúrgico envolve responsabilidades do hospital, da equipe de saúde, do paciente e familiares em diversos graus, e para resultados pós-operatórios positivos, o adequado preparo do paciente tem fundamental importância (1)(2)(3)(4)(5) .…”
Section: Introductionunclassified
“…Patients who read their notes, collect their personal health data, and maintain a record are more engaged, empowered, and activated to participate in their healthcare. One study found that patients with hip and knee arthritis who had higher levels of patient engagement preoperatively were more likely to achieve greater pain relief and satisfaction after total joint arthroplasty [1].…”
mentioning
confidence: 99%